Determinants of internal audit contribution to strategic management: Malaysian evidences - Zainal Abidin , Nor Hafizah; Haron, Hasnah; Shahbudin, Amirul Shah (2011)
This paper examines from agency perspective how internal audit experience, audit committee attributes, risk management and control systems influence internal audit contribution to strategic management. The study analysed data collected from 117 head of internal audit function in public listed companies on Bursa Malaysia. Internal audit experience, audit committee qualification, audit committee review, risk management and control systems are found to be significantly positively related to internal audit contribution to strategic management. Findings indicate that audit committee concern is not a significant predictor of internal audit contribution to strategic management. This paper has provided empirical evidences to support the findings from previous qualitative studies. Besides, this study has enhanced the understanding of predictors of internal audit contribution to strategic management in a context of mandatory environment.